An extracellular mechanism that can explain the neurotoxic effects of α-synuclein aggregates in the brain - Pacheco, Carla; Aguayo, Luis G.; Opazo, Carlos (Frontiers in Physiology, 2012)
Neurodegenerative diseases, such as Parkinson's disease (PD), Alzheimer’s disease (AD) and Dementia with Lewy bodies, display an accumulation of proteins including α-synuclein aggregates in cortical and subcortical regions of the brain. PD is a complex, progressive disease which involves damage of motor and cognitive brain regions, as well as autonomic and sensory areas. Since α-synuclein is a neuronal cytosolic protein, it is assumed that pathogenic changes induced by α-synuclein aggregates occur only at the cytoplasmic level. However, recent studies have identified the presence of extracellular α-synuclein, suggesting that the pathogenic action of this protein may also occur in the extracellular milieu through an unknown mechanism. One of the hyphotheses is that extracellular α-synuclein aggregates or oligomers may directly disrupt the neuronal membrane by the formation of a pore reminiscent to the ones formed by β-amyloid aggregates. Here, we will review some evidence that support this mechanism, analyzing the interactions of α-synuclein with components of the plasma membrane, the formation of pore/perforated structures and the implications on ionic dyshomeostasis. Furthermore, we will also discuss how this mechanism can be integrated into a general phenomenon that may explain the synaptotoxicity and neurotoxicity observed in different neurodegenerative diseases.